Experimental study on a precast beam-column joint with double grouted splice sleeves. (15th November 2019) - Lu, Zhiwei; Huang, Jun; Dai, Shaobin; Liu, Jixiong; Zhang, Mingzhong
Highlights: A precast beam-column joint connected by double grouted sleeves is proposed. The seismic behaviour of the joint under static and cyclic loadings was investigated. The load carrying capacity of the joint is similar to that of the cast-in-place specimen. The ductility and energy dissipation are improved with increasing assembly length. The bearing and energy dissipation capacities increase with increasing transition bar diameter. Threads in the sleeve have a negative impact on the ductility and energy dissipation. Abstract: The construction speed and quality of precast frame structures are greatly influenced by weld, tie, prestress, cast concrete requirements, etc. on site. To address these challenges, a precast beam-column joint connected by double grouted sleeves is proposed. This paper presents an investigation on seismic behaviour of the joint subjected to static and cyclic loadings. In total, six precast specimens with different assembly lengths, transition bar diameters and types of grouted sleeve and one cast-in-place control specimen were tested. Results show that the double grouted sleeve splices in joints perform well. The initial stiffness of prefabricated specimens is larger than that of the control specimen and the load bearing capacity of the prefabricated specimens is similar to that of the control specimen. As the transition rebar diameter increases from 16 mm to 18 mm, the energy dissipation ability of the prefabricated specimens is increased by 64.8% but is approximately 41% lower than that of the control specimen due to their relatively lower deformation capacity. Threads in the grouted sleeve have a negative impact on the deformation and energy dissipation abilities of the joints. The method for cast-in-situ joint is adequate for predicting the flexural capacity of precast joint connected by double grouted sleeves.